Evaluation of the effects of two different Alt-RAMEC procedures: five weeks versus nine weeks - Celikoglu Mevlut; Buyukcavus Muhammet Hilmi (Sciendo, 2017)
To evaluate and compare the skeletal, dentoalveolar and soft tissue effects of two different alternate rapid maxillary expansion (RMEs) and constriction (Alt-RAMEC) procedures.